Pancasila dan kearifan lokal: Sinergi paradigma dalam membangun identitas dan ketahanan budaya bangsa - Ramadhan, Revan Hilalfi (Maliki Interdisciplinary Journal, 2025)
The identity and cultural resilience of the Indonesian nation in the era of globalization face complex challenges. This study aims to analyze the paradigmatic synergy between Pancasila as the foundation of the state and local wisdom as the roots of culture in building national identity and cultural resilience. The research method used is qualitative with a literature study approach, in which data is analyzed descriptively and critically. The findings reveal that the values of Pancasila (Belief in God, Humanity, Unity, Democracy, and Justice) are universal and resonate with the principles that live in various local wisdom of the archipelago. This synergy is not a hierarchical relationship, but rather a mutually complementary and reinforcing one; Pancasila provides a national philosophical framework, while local wisdom provides concrete and contextual cultural manifestations. The conclusion of this study affirms that the integration of Pancasila and local wisdom forms a dynamic paradigm of cultural resilience. This paradigm not only preserves cultural heritage but also empowers it as a foundation for facing global change, thereby strengthening an inclusive and sustainable national identity. This synergy ultimately becomes an important pillar in strengthening the character of the nation and national resilience as a whole.